Obtenção, caracterização e atividade antitumoral in vitro de bromelina de diferentes partes de abacaxizeiros - Miranda, Íngara Keisle São Paulo Barretto (2014)
Bromelain is an enzyme complex with great therapeutic importance attributed both to it’s proteolytic activity, as the non-proteolytic components in the extract. Thus, the enzyme was extracted from different parts of Ananas comosus var comosus, from two pineapple with different codes: BGA 771 and BGA 772. The proteolytic and specific activities of bromelain from each part (stem, crown, peel, pulp and leaves) were investigated as well as their kinetic characteristics by measuring the optimum temperature and the optimum pH, and finally was studied it’s effect in vitro on murine melanoma B16F10 cells. In BGA 771, the highest proteolytic activity was found in the stem (81.10 mg/mL/min), while the highest specific activity was found in the pulp and peel (1983.44 and 1822.33 UA/mg of bromelain, respectively). In general, the optimum temperature varied between of 50 to 80 °C and pH between 6 and 8. Bromelain all parts were effective more than 50% in inhibiting the melanoma B16F10 cells proliferation after 48 hours. The most significant inhibition was find on crown bromelain with 72.86%, and a time-dependent effect was observed on crown bromelain. At BGA 772 the higher activity was find in the pulp (35.58 mg/mL/min and 1446.60 UA/mg bromelain). The optimum temperature in the extracts ranged between 40 and 90 °C, while the pH 6 was the best for all parties, while the leaf bromelain had two great points: 6 and 8. Only the bromelain peel was able to inhibit the melanoma B16F10 proliferation of, being 66.37% after 48 hours of contact, and a dose-dependent activity was observed.